ANALISIS SIFAT FISIS DAN MEKANIK PADA BETON DENGAN BAHAN TAMBAH ADMIXTURE FOSROC SP310 - Aryanto, Dimas Agus; Priyanto, Kusdiman Joko; Sungkono, Kukuh Kurniawan Dwi (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2025)
Concrete is a primary construction material widely used across the world. It is a composite material composed of sand, gravel (coarse aggregate), Portland cement, and water. To improve its quality and accelerate the hardening process, additives are often incorporated. One such additive is Fosroc SP310, a type of superplasticizer. This admixture enhances concrete performance and reduces the risk of structural damage due to corrosion. This study investigates the effect of various dosages of Fosroc SP310—0.5%, 1%, 1.2%, and 1.5% by weight of cement. A total of 60 cylindrical specimens measuring 10 cm × 20 cm were prepared for compressive strength testing at curing ages of 3, 7, 14, and 28 days. The results show that normal concrete exhibited a compressive strength ranging from 24.60 MPa (14 days) to 48.44 MPa (3 days). With 0.5% admixture, strength ranged from 25.46 MPa (7 days) to 47.05 MPa (3 days). At 1%, values ranged from 23.15 MPa to 48.44 MPa. The 1.2% dosage yielded the highest strength: 54.26 MPa (14 days) and 41.80 MPa (28 days), compared to 29.71 MPa for normal concrete at 28 days. It can be concluded that the 1.2% dosage is most effective in enhancing compressive strength